2021
DOI: 10.3389/fvets.2021.659771
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Tissue Distribution of Chelerythrine and Effects of Macleaya Cordata Extracts on Liver NAD(P)H Quinone Oxidoreductase

Abstract: Background:Macleaya cordata (Willd.) (Papaveraceae) is listed as a feed additive in animal production by the European Food Authority.Methods: The metabolites of chelerythrine in rats were measured in vitro and in vivo by rapid and accurate high-performance liquid chromatography/quadrupole-time-of-flight mass spectrometry (HPLC/QqTOF-MS). The structures of CHE metabolites were elucidated by comparing their changes in accurate molecular masses and fragment ions with those of parent ion or metabolite. The metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Sanguinarine along with chelerythrine are known as main effective alkaloids of Macleaya cordata [ 26 ]. Sangrovit ® is a low-cost, safe, and effective feed additive derived from Macleaya cordata , with sanguinarine and chelerythrine as the major bioactive compounds [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sanguinarine along with chelerythrine are known as main effective alkaloids of Macleaya cordata [ 26 ]. Sangrovit ® is a low-cost, safe, and effective feed additive derived from Macleaya cordata , with sanguinarine and chelerythrine as the major bioactive compounds [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the current study showed that treatment with MCE reduced the AST, ALT, and LDH activity and increased the ALP activity in HS-induced broilers, suggesting that MCE seems to protect the broilers from liver injury. The protective effect of MCE on the liver may be due to the inhibition of hepatic NAD(P)H quinone oxidoreductase activity [ 62 ] and the hepatic lipid peroxidation and inflammatory response [ 63 ] by chelerythrine. Moreover, HS also significantly decreased the levels of serum GLU and significantly increased the levels of TC and LDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, MCE administration attenuated HS-mediated liver damage, evidenced by serum’s reduction in AST and ALT activities. The protective effect of MCE on the liver may be due to the inhibition of hepatic NAD(P)H quinone oxidoreductase activity [ 52 ] and the hepatic lipid peroxidation and inflammatory response [ 53 ] by chelerythrine.…”
Section: Discussionmentioning
confidence: 99%